CERAMAH INTERAKTIF DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR: DAMPAK TERHADAP PEMAHAMAN DAN PARTISIPASI SISWA - TIA AULIA (CV. ADIBA AISHA AMIRA, 2026)
Thematic learning in elementary schools requires instructional methods that can enhance both students’ understanding and active participation. One method that can be applied is the interactive lecture method. This study aims to determine the impact of using interactive lectures in thematic learning on students’ understanding and participation in elementary schools. The interactive lecture method is a teaching approach that combines teacher explanations with active interaction between teachers and students through question-and-answer sessions, short discussions, and examples related to students’ daily lives. The results of the study indicate that the use of interactive lectures helps students understand learning materials more easily because the teacher not only explains but also involves students in the learning process. In addition, this method increases student participation as they are given opportunities to ask questions, answer questions, and express their opinions. Thus, the learning atmosphere becomes more active and engaging. Based on these findings, it can be concluded that the implementation of the interactive lecture method in thematic learning at the elementary school level has a positive impact on improving students’ understanding and participation. Therefore, this method can serve as an effective alternative teaching strategy for teachers in the classroom.